Isolasi dan Identifikasi Endomikoriza pada Perakaran Tanaman Jagung (Zea mays L.) Dataran Sedang serta Perbanyakannya pada Tingkat Kadar Air Tanah Berbeda - WEDAGAMA, NGAKAN MADE ADI; SUKEWIJAYA, I MADE; KARTINI, NI LUH; RAI, I NYOMAN (Agrotrop : Journal on Agriculture Science; Vol 9 No 2 (2019), 2019)
Isolation and Identification of Endomycorrhizal on Corn Root (Zea mays L.) at Medium Plain and its Propagation at Different Soil Water Level. Endomycorrhizal has several benefits that can increase the absorption of water and nutrients, protect plants from root pathogens and toxic elements, play a role in the improvement of soil structure, and increase the solubility of nutrients. The purpose of this research is to find out the types endomycorrhizal contained in the corn roots at medium plains in Gianyar Regency, and the influence of different soil water level to endomycorrhizal ability to reproduce spores. This research was conducted from September 2017 to February 2018. The method of the research includes exploration, isolation, identification, propagation of spores endomycorrhizal, and soil samples analysis. Isolation and identification result found 2 genus of spores endomycorrhizal that was Glomus and Acaulospora, with various spore amount and the level of infection endomycorrhizal was very high with percentage of 83.33-86.67%. Spores propagation test results showed that the highest percentage enhacement of spores endomycorrhizal amount was found in the third soil sampling location in soil water level of 40% field capacity treatment with percentage of 551.85%. The level of endomycorrhizal infections at the roots of all treatment of soil sampling location and soil water level were very high with percentage of 100%.